Composite non-destructive evaluation system for probability of detection assessment. (1st January 2011) - Guo, Yan; Yang, Kai
In non-destructive evaluation (NDE) studies, the probability of detection (POD) curve is an important performance metric for an NDE system. POD curve estimation and NDE capability assessment are based on the flaws detected and the flaws missed. In order to get the information of undetected flaws, fabricated artificial flaws are often used which provide complete information of defects in most of laboratory demonstrations. However, this practice is too expensive and impractical to use in the field environment. In this study, a combination of several additional NDE inspection systems, called composite NDE system, is proposed to assist the POD evaluation based on field inspection. A simulation model is built to evaluate the effectiveness of the composite NDE system. The simulation result of this approach is verified and compared with traditional POD evaluation methods.